Pipe welding - Jeffus, Larry; Baker, Bryan (Singapore : [no publisher identified], 2020)
Pipe welding is a comprehensive classroom/shop text-book designed to turn a skilled plate welder into an employable pipe welder.
CHAPTER 1. Introduction to Pipe Welding -- 2. Welding Safety -- 3. Shop Math -- 4. Blueprint Reading and welding symbols -- 5. Thermal-Cutting Processes -- 6. Pipe Joint Design and Preparation -- 7. Pipe Fit-Up and Alignment -- 8. Shielded Metal Arc -- 9.Gas Metal Arc Welding of Pipe -- 10. Flux Cored Arc Welding of Pipe -- 11. gas Tungsten Arc Welding of Pipe -- 12. Pipe Welding with multiple processes -- 13. Machine and Automatic pipe welding -- 14. Filler Metals -- 15. Welding Metallurgy -- 16. Weld Discontinuities and defects -- 17. Pipe Weld Repairs -- 18. Testing and inspecting welds -- 19. Pipe welding certification welding procedures -- 20. Pipe threads.
Includes index.
Keywords: WELDING